Development of properties database of carbon dioxide refrigerant - Mohd. Hazim Che Hassan, author; Henry Nasution, supervisor; Fakulti Kejuruteraan Mekanikal (2012)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2012